How "big" should government be? - António Afonso; Ludger Schuknecht (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
We assess how "big" government should reasonably be in a number of advanced countries. First, we will link the recent findings of Data Envelope Analysis on efficient public expenditure with the question of the size of the government. Second, we report descriptive analysis of various government performance indicators in relation to public expenditure to provide indications of overall "optimal" across spending categories. In principle, the highest savings potential is in the biggest expenditure categories, public consumption and social expenditure.
Keywords: 330